A qualitative study of pharmacists’ perceptions and awareness of homoeopathic medicines in Durban, South Africa - Nokuthula H. Mavela; Ingrid M.S. Couchman; Themba Mgwaba; Celenkosini T. Nxumalo (South African Family Practice)
Background: There is growing interest in the demand for and use of homoeopathic medicines by the public; however, little is known about the perspectives of pharmacists regarding the use of these medicines, particularly in the South African private health context.